Cocoa liquor increases SOD activity in wistar rats experiencing oxidative stress - Kartika Wahyu Dwi Putra; Bambang Wirjatmadi; Bambang Purwanto; Merryana Adriani (Health Notions, 2018)
Chocolate is a healthy food. The active ingredient in chocolate (Theobroma cacao L.), especially antioxidants, can counteract the free radicals present in the body. This study aimed to determine the effect of cocoa liquor on increased activity of Superoxyde Dismutase (SOD). The study design was randomized post test only control group with 20 samples of male white rats wistar (Rattus norvegicus). The sample was divided into 4 groups: 2 control groups and 2 treatment groups. The treatments provided were instantaneous physical activity and cocoa liquor preparation with a single dose. This study used one way anova and continued with post hoc tukey HSD test for statistic. The results showed that cocoa liquor had an effect on SOD activity. SOD activity increased in treatment group with cocoa liquor either 2 hours or 24 hours before the momentary physical activity. Keywords: Cocoa liquor, Superoxide dismutase, Oxidative stress